Relationship between psychological adaptability and work engagement of college teachers within smart teaching environments: the mediating role of digital information literacy self-efficacy - Fan, Shiyi; Yu, Zeyuan; Zheng, Xin; Gao, Chunhai (Frontiers in Psychology, 2023)
This study aims to analyze the relationship between the psychological adaptability and work engagement of college teachers underin a smart teaching environment. Applying structural equation modeling (SEM) to a sample of 373 front-line teachers, this study focuses on the mediating effect of digital information literacy self-efficacy on the relationship between teachers’ psychological adaptability and work engagement. The results show that the four dimensions of college teachers’ psychological adaptability have distinct influences on different aspects of work engagement and digital information literacy self-efficacy. In particular, teachers’ psychological adaptability and work engagement are positively correlated; teachers’ self-efficacy can positively affect the three dimensions of their work engagement; and teachers’ psychological adaptability can positively affect their digital information literacy self-efficacy. The above results can serve as a basis for the development and improvement of the training of college teachers and the implementation of smart teaching.